Soil organic matter and soil structure changes with tillage practices and straw incorporation in a saline-sodic soil - Laghari, Azhar Ali; Abro, Quart-ul-ain; Leghari, Asma; Kumar, Akash; Kumari, Lata; Nindwani, Barkat Ali; Gull, Sadia (Frontiers in Plant Science, 2025)
Soil salinity and sodicity pose significant challenges to sustainable agriculture by adversely affecting soil properties, crop growth, and yield. The study was conducted in an agricultural field located in Khipro, within the Sanghar district of Sindh Province, Pakistan, to assess the impact of tillage practices and wheat straw incorporation on the organic matter content and structural properties of saline-sodic soil. Field experiments were conducted under shallow (ST) and deep tillage (DT) systems, a conventional practice (NPK fertilizer with gypsum, CK), a control (no straw or gypsum, CTRL), and three wheat straw application rates of 3, 7, and 10 Mg ha−¹ and gypsum application rates corresponding to 25%, 50%, and 75% of the gypsum requirement (GR). After two years, soil organic matter (SOM), water-stable aggregates (WSA), mean weight diameter (MWD), and aggregate stability (AS) were significantly improved (P ≤ 0.05) in treatments with incorporated wheat straw. Compared with the control, the combined application of deep tillage, 10 Mg ha−¹ straw, and 75% gypsum increased soil organic matter by approximately 35%, water-stable aggregates (>0.25 mm) by 12–18%, aggregate stability by 42%, and mean weight diameter by 31%. Improvements were more pronounced in the upper 0–15 cm soil layer than in deeper layers. Enzymatic activities, including dehydrogenase, urease, and alkaline phosphatase, also increased by 28–46% under the same treatment, indicating enhanced microbial activity and nutrient cycling. These findings demonstrate that integrating straw incorporation with deep tillage and gypsum amendment is an effective management practice to improve soil structure, organic matter content, and biological activity in saline-sodic soils under semi-arid conditions.